2022
DOI: 10.1007/s00240-022-01365-8
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of ureteral obstruction after percutaneous nephrolithotomy

Abstract: Background Ureteral obstruction after percutaneous nephrolithotomy (PCNL) may require prolonged drainage with a nephrostomy tube (NT) or ureteral stent, but it is not well understood how and why this occurs. The goal of this study was to identify risk factors associated with postoperative ureteral obstruction to help guide drainage tube selection. Methods Prospective data from adult patients enrolled in the Registry for Stones of the Kidney and Ureter (ReS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 12 publications
0
9
1
Order By: Relevance
“…In our study, 20% of patients treated with mPCNL showed ureteral obstruction during percutaneous pyelography on POD2. This rate is lower compared to that reported in a series of 241 standard PCNL, in which Authors found that 31.5% of patients had impaired ureteral canalization on POD1 [ 7 ]. Our results might differ from those in published literature for several reasons.…”
Section: Discussioncontrasting
confidence: 55%
See 4 more Smart Citations
“…In our study, 20% of patients treated with mPCNL showed ureteral obstruction during percutaneous pyelography on POD2. This rate is lower compared to that reported in a series of 241 standard PCNL, in which Authors found that 31.5% of patients had impaired ureteral canalization on POD1 [ 7 ]. Our results might differ from those in published literature for several reasons.…”
Section: Discussioncontrasting
confidence: 55%
“…Nonetheless, early postoperative complications can occur even after uneventful mPCNL, thus neutralizing the advantages of a tubeless procedure or an early discharge [ 17 ]. Among these, transient upper urinary tract obstruction due to post-PCNL edema, in patients without urinary drainage, can cause severe pain, kidney function impairment, and hospital readmission [ 7 ]. For this reason, it is of primary clinical importance to identify patients at higher risk of ureteral obstruction, in order to improve the selection of totally tubeless mPCNL procedures.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations